Beating uncontrolled eating: Training inhibitory control to reduce food intake and food cue sensitivity. (1st December 2018) - Oomen, Danna; Grol, Maud; Spronk, Desiree; Booth, Charlotte; Fox, Elaine
Abstract: In our food-rich environment we must constantly resist appealing food in order to maintain a healthy lifestyle. Previous studies have found that food-specific inhibition training can produce changes in eating behaviour, such as a reduction in snack consumption. However, the mechanisms that drive the effect of inhibition training on eating behaviour remain unknown. Identifying the mechanism underlying food-specific inhibition training could lead to more targeted training interventions increasing the potential efficacy of such interventions. In the current study, we investigated directly whether training-induced effects on inhibitory control might underlie the predicted change in eating behaviour. Healthy individuals who scored high on uncontrolled eating were randomly assigned to receive six online training sessions over six consecutive days of either food-specific response inhibition training (active group; n  = 21) or response inhibition training without food stimuli (control group; n  = 20). We measured pre- and post-training inhibitory control in the context of food and food cue sensitivity, as well as food consumption in a bogus taste test. As expected, food-specific inhibition training decreased snack consumption in the bogus taste test relative to control training. However, the active training did not improve inhibitory control towards food, nor did it reduce food cue sensitivity above and beyond the control training. Future studies are needed to investigate the potential underlying mechanism of food-specific inhibition training, as it remains unclear what drives the reliable effect on eating behaviour.